1997
DOI: 10.1128/jvi.71.2.1453-1465.1997
|View full text |Cite
|
Sign up to set email alerts
|

The CD4-independent tropism of human immunodeficiency virus type 2 involves several regions of the envelope protein and correlates with a reduced activation threshold for envelope-mediated fusion

Abstract: Several human immunodeficiency virus type 2 (HIV-2) strains have been shown to infect some CD4-negative cell lines (P. R. Clapham, A. McKnight, and R. A. Weiss, J. Virol. 66:3531-3537, 1992). Using molecular clones of HIV-2 with a CD4-independent tropism, we have identified critical amino acid residues in the envelope protein which are required for CD4-independent infection. Mutations located immediately upstream of a proposed coiled coil domain in the transmembrane protein (A526T or I528M) and flanking the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 77 publications
(121 reference statements)
2
27
0
Order By: Relevance
“…Lentivirus transmission to new species has been studied mainly in relation to host-encoded restriction factors. Nevertheless, the study of HIV Env mutants responsible for the infection of cells lacking the CD4 virus receptor provided evidence that important mutations were not located only in SU subunit, where subsequently a coreceptor binding site was revealed, but also some mutations were located in TM subunit (gp41) (49). Similarly, mutations in gp41 influence the virus infectivity and fusogenic activity (50).…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus transmission to new species has been studied mainly in relation to host-encoded restriction factors. Nevertheless, the study of HIV Env mutants responsible for the infection of cells lacking the CD4 virus receptor provided evidence that important mutations were not located only in SU subunit, where subsequently a coreceptor binding site was revealed, but also some mutations were located in TM subunit (gp41) (49). Similarly, mutations in gp41 influence the virus infectivity and fusogenic activity (50).…”
Section: Discussionmentioning
confidence: 99%
“…The CD4-independent HIV Env (mNDK and ROD/B) expression plasmids were kindly provided by Dr. U. Hazan [4] and Dr. P. R. Clapham [49]. The CD4-dependent HIV-1 Env (HXB2 strain) expression plasmid was kindly provided by Dr. Y. Yokomaku.…”
Section: Expression Plasmidsmentioning
confidence: 99%
“…The diverse cell tropism among different isolates was attributed to the differential use of chemokine receptors by HIV (31,32). Although some HIV isolates are CD4-independent strains, the coreceptor is absolutely required (33)(34)(35)(36), suggesting that the coreceptor in HIV entry into target cells has an essential function. It has been demonstrated that conformational changes triggered on the CD4 engagement are not sufficient to drive fusion (37)(38)(39).…”
Section: Coreceptor For Hiv-1 Env Conformational Changesmentioning
confidence: 99%